Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1039/c2fo30259d
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive properties of raisins originating from Greece in colon cancer cells

Abstract: Colorectal cancer is one of the major causes of cancer-related mortality in humans in both developed and developing countries. Dietary patterns influence the risk of colon cancer development, while plant-derived foods have gained great interest, due to the high content of antioxidants. Corinthian raisins (Currants, CR) and Sultanas (S) (Vitis vinifera L., Vitaceae) are dried vine fruits produced in Greece with many culinary uses in both the Mediterranean and the Western nutrition. In the present study, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 44 publications
0
29
1
2
Order By: Relevance
“…Moreover, studies have shown that it may act as an inhibitor of cancer development [77][78][79] . The mechanisms explaining resveratrol's anti-inflammatory properties have been reviewed by de la Lastra et al [80] .…”
Section: Resveratrolmentioning
confidence: 99%
“…Moreover, studies have shown that it may act as an inhibitor of cancer development [77][78][79] . The mechanisms explaining resveratrol's anti-inflammatory properties have been reviewed by de la Lastra et al [80] .…”
Section: Resveratrolmentioning
confidence: 99%
“…On the other hand, V. vinifera extract effect decreases in lower concentrations (5-50 μg/mL). Different parts of V. vinifera have been widely investigated against different types of cancer (Kaliora et al 2008;Amico et al 2009;Lazze et al 2009;Sung & Lee 2010;Nechita et al 2012;Apostolou et al 2013;Esfahanian et al 2013;Espino et al 2013;Kountouri et al 2013;Giovannelli et al 2014;Liang et al 2014;Sahpazidou et al 2014) and it has been reported that V. vinifera has an antiproliferative effect against many cancer cell lines. Naturally occurring bioactive component of V. vinifera that is responsible from the cardioprotective and cancer chemopreventive activities (Jang et al 1997) is identified as resveratrol (3,4 ,5-trihydroxystilbene) (Frankel et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Raisins are also rich in phytochemicals, which may convey protection against colorectal [16] and gastric [18] cancer and may also play a role in the prevention of cardiovascular disease through a triglyceride-and cholesterollowering effect [19]. They have also been reported to provide protection against diabetes by lowering the postprandial insulin response and modulating sugar absorption [20].…”
Section: Health Aspectsmentioning
confidence: 97%
“…As raisins are a rich source of fiber, a single serving of raisins provides a significant amount of fiber in a daily diet and can have beneficial effects on colon health [16]. Moreover, evidence suggests that dietary fiber may act synergistically with tartaric acid in raisins to stimulate the growth and/or activity of bacteria in the digestive system in ways claimed to be beneficial to health [17].…”
Section: Health Aspectsmentioning
confidence: 99%